2021
DOI: 10.1016/j.rinam.2021.100145
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and mathematical analysis of the outbreak of coronavirus (COVID-19) in Bangladesh

Abstract: In this study based on Bangladesh, a modified SIR model is produced and analysed for COVID-19. We have theoretically investigated the model along with numerical simulations. The reproduction number has been calculated by using the method of the next-generation matrix. Due to the basic reproduction number, we have analysed the local stability of the model for disease-free and endemic equilibria. We have investigated the sensitivity of the reproduction number to parameters and calculate the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In terms of recovered cases, the number of recovered people has increased since October 2021 ( Figure 3 ). A previous study in Bangladesh by applying the SEQIRP model (modified SIR model) observed that, after 400 days (April 2021), the actual recovery rate was increasing, with a value of roughly 0.56 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of recovered cases, the number of recovered people has increased since October 2021 ( Figure 3 ). A previous study in Bangladesh by applying the SEQIRP model (modified SIR model) observed that, after 400 days (April 2021), the actual recovery rate was increasing, with a value of roughly 0.56 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parsamanesh and Erfanian [ 20 ] looked at the global dynamics of a model with a standard incidence rate and immunization approach. Shahrear et al [ 21 ] have predicted and mathematically analyzed the COVID-19 outbreak in Bangladeshi scenario, and Maugeri et al [ 22 ] have analyzed the transmission of the COVID-19 pandemic in Saudi Arabia and Indonesia. By eliciting behavioural reactions in the community, Saha et al [ 23 ] explored an epidemic model of the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Dauda et al [ 3 ] on the other hand focused on Plateau State with emphasis on statistical analysis of lockdown, locus of control and state anxiety among residents. Furthermore, while some studies focused on hybrid fractional order, fractional optimal control and stochastic models [ 13 16 ], some other recent studies predicted outbreak of coronavirus and assessment of control measures as well as Neyman–Scott point process model for COVID-19 both within and across international borders [ 17 20 ]. However, from the foregoing researches and other previously published works [ 21 27 ], there has not been any published research to date which has considered a mathematical model approach for the transmission dynamics of the spread of COVID-19 in Plateau State Nigeria.…”
Section: Introductionmentioning
confidence: 99%